Study the Role Serum Omentin-1 in Occurrence and Development of Diabetic Retinopathy (Medico Legal Update, 2020)
Diabetic retinopathy (DR) is a retinal disease which is one of the most severe micro vascular complicationsoccurring due to diabetes mellitus and is a major cause of blindness. The aim of this work was to studythe serum level of omentin-1 and its relation to diabetic retinopathy in type 2 diabetes mellitus. Thestudy included 60 diabetic patients (30 patients T2DM complicated with DR and 30 patients T2DM notcomplicated with DR). The study also included 30 healthy control individuals defended as subjects whoapparently haven’t any chronic diseases. Thorough history taking and physical examination with calculationof body mass index (BMI), investigations were done including HbA1c, C-reactive protein (CRP) andserum omentin-1. Fundus examination was carried out by an expert ophthalmologist. The study showedthat serum omintin-1 was reduced significantly (P